Woody Plant Declines. What's Wrong with the Microbiome?. (April 2020) - Bettenfeld, Pauline; Fontaine, Florence; Trouvelot, Sophie; Fernandez, Olivier; Courty, Pierre-Emmanuel
Abstract : Woody plant (WP) declines have multifactorial determinants as well as a biological and economic reality. The vascular system of WPs involved in the transport of carbon, nitrogen, and water from sources to sinks has a seasonal activity, which places it at a central position for mediating plant–environment interactions from nutrient cycling to community assembly and for regulating a variety of processes. To limit effects and to fight against declines, we propose: (i) to consider the WP and its associated microbiota as an holobiont and as a set of functions; (ii) to consider simultaneously, without looking at what comes first, the physiological or pathogenic disorders; and (iii) to define pragmatic strategies, including preventive and curative agronomical practices based on microbiota engineering. Highlights: WPs provide several ecosystem services such as climate regulation, nutrient cycling, carbon sink, production, reservoir of biodiversity, and creative and cultural added values. WP diseases or diebacks result from the combination of various factors (e.g., abiotic factors, fungi, bacteria, inadequate technical practices, and also unidentified ones). Microbial communities associated with plants are complex and dynamic, with mutualistic and commensal species that coexist with pathogenic species. Declines could be related to microbiome modifications or imbalance, meaning that essential functions for keeping the holobiont fitness are not covered. The selection and engineering of microbiota based on their ecosystem services, targeting some declines resulting from microbiome and interaction analysis, will ensure promising tools to improve WP health and management.